Genomic and non-genomic effects of androgens in the cardiovascular system: clinical implications - Lucas-Herald, Angela K; Alves-Lopes, Rheure; Montezano, Augusto C; Ahmed, S Faisal; Touyz, Rhian M (Clinical science (1979), 2017)
The principle steroidal androgens are testosterone and its metabolite 5α-dihydrotestosterone (DHT), which is converted from testosterone by the enzyme 5α-reductase. Through the classic pathway with androgens crossing the plasma membrane and binding to the androgen receptor (AR) or via mechanisms independent of the ligand-dependent transactivation function of nuclear receptors, testosterone induces genomic and non-genomic effects respectively. AR is widely distributed in several tissues, including vascular endothelial and smooth muscle cells. Androgens are essential for many developmental and physiological processes, especially in male reproductive tissues. It is now clear that androgens have multiple actions besides sex differentiation and sexual maturation and that many physiological systems are influenced by androgens, including regulation of cardiovascular function [nitric oxide (NO) release, Ca mobilization, vascular apoptosis, hypertrophy, calcification, senescence and reactive oxygen species (ROS) generation]. This review focuses on evidence indicating that interplay between genomic and non-genomic actions of testosterone may influence cardiovascular function.